2016
DOI: 10.1016/j.isprsjprs.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing selection of training and auxiliary data for operational land cover classification for the LCMAP initiative

Abstract: 15The U.S. Geological Survey's Land Change Monitoring, Assessment, and Projection (LCMAP) initiative 16 is a new end-to-end capability to continuously track and characterize changes in land cover, use, and 17 condition to better support research and applications relevant to resource management and environmental 18 change. Among the LCMAP product suite, there are annual land cover maps that will be available to the 19 public. This paper describes an approach to optimize the selection of training and auxiliary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 73 publications
(49 reference statements)
2
103
0
Order By: Relevance
“…CCDC models were fit to time series of Tasseled Cap Greenness observations from the 2005-2015 base period using a Fourier-style regression model. We chose to use harmonic regression over other non-parametric models and data filters because harmonic models (1) characterize general seasonal patterns across years, (2) produce a fitted equation for each pixel that can be used for predicting images at any given day of year, and (3) are becoming more widely used for operational monitoring of land cover, condition, and change [27,28,34,35]. The models used in this study included 12-month and 4-month harmonics based on the following functional form:…”
Section: Historic Model Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…CCDC models were fit to time series of Tasseled Cap Greenness observations from the 2005-2015 base period using a Fourier-style regression model. We chose to use harmonic regression over other non-parametric models and data filters because harmonic models (1) characterize general seasonal patterns across years, (2) produce a fitted equation for each pixel that can be used for predicting images at any given day of year, and (3) are becoming more widely used for operational monitoring of land cover, condition, and change [27,28,34,35]. The models used in this study included 12-month and 4-month harmonics based on the following functional form:…”
Section: Historic Model Fittingmentioning
confidence: 99%
“…In Southern New England, gypsy moth has persisted at relatively low population densities since the 1980s, therefore, we assume an 11-year stable base period leading up to our 2016 monitoring period. In other parts of the country such as the central Appalachian Mountains, defoliation events may have occurred more frequently in previous decades [35,39]. In these places, harmonic models could be fit to the subset of years with lower defoliation.…”
Section: Generalization In the Spatial And Temporal Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…For training, a minimum of 600 pixels for any class was found to provide the best classification result [30]. For several of the 14 path/rows the limited number of LC Trends blocks available did not provide class populations of 600 pixels for one or more classes (for example, see Table 10a for Montana and Arizona).…”
Section: Discussionmentioning
confidence: 99%
“…We extracted training data from LC Trends blocks based on criteria developed from an analysis of best practices [30]. That analysis found that a total of 20,000 pixels distributed across classes in proportion to the LC Trends class distribution was optimal, with a minimum of 600 pixels and a maximum of 8000 pixels required for each class (note, if the total number of pixels for a given class was less than 600, we extracted all available pixels).…”
Section: Ccdc Annual Land Covermentioning
confidence: 99%